Workshop Pentingnya Tertib Administrasi Keuangan Dalam Tata Kelola Dana Desa - Mulyadi, Mulyadi; Mahendra, Candra; Prutama, Muhamad Julyyo; Rolanda , Deky; Harpudin, Harpudin (Universitas Dehasen Bengkulu, 2021)
This paper discusses the importance of workshops in raising awareness of village fund governance and the importance of sound financial administration in that context. Village funds are a vital resource for local development, and their effective management requires a deep understanding of the principles of good financial administration. The workshops offered address various aspects, from financial reporting to risk management, and provide an understanding of the importance of transparency and accountability in the management of village funds. Through active participation in these workshops, it is hoped that stakeholders at the village level can improve their skills and knowledge in managing village funds more efficiently and accountably, which in turn will support sustainable local development.